IMPROVING STUDENTS’ LANGUAGE PROFICIENCY THROUGH READING (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
The importance of reading for students in developing their language proficiency has received a lot of attention in the field of language education. Using a variety of empirical studies and theoretical frameworks, this article offers a thorough review and analysis of the effectiveness of using reading as a tool to improve students' language proficiency.